The thiazole and triazole derivatives as inhibitors of metal corrosion: Part I - Jelena Nakomčić; Đenđi Vaštag (Zaštita Materijala, 2016)
This review is a result of the literature survey concerning the possibility of inhibition of steel and aluminum alloy corrosion in different conditions using organic compounds. As it is well known, in the most cases, molecules which contain hetero atoms as nitrogen, sulfur and oxygen exhibit good inhibition properties against metal corrosion. Thiazole and triazole derivatives belong to the group of compounds which exhibits inhibition properties against metal corrosion in different media. There are some new investigation techniques as well as the new research approaches and new methods of inhibitor application that are developed recently.